Paulos Mar Gregorios : A Reader - Gregorios, Paulos Mar (Book collections on Project MUSE., 2018)
Paulos Mar Greogorios: A Reader is a compilation of the selected writings of Paulos Mar Gregorios, a metropolitan of the Malankara Orthodox Syrian Church of India and a former President of the World Council of Churches. The book deals with his thought in the areas of ecumenism, orthodox theology, philosophy, interfaith dialogue, and philosophy of science. The book will be of special value to the students of ecumenism, Eastern and Oriental Orthodoxy, Indian philosophy, interdisciplinary studies, and holistic education.